Računalniško krmiljeno preizkuševališče za raziskavo materialov mehanskih drsnih tesnil - Vezjak, Anton (Materiali in tehnologije, 2000)
Mechanical seals are dynamic shaft seals in which primary sealing takes place between surfaces in sliding contact of two mated seal faces. The most important aspect of development of mechanical seal is the tribological design of the seal faces. Seal faces are exposed to severe conditions which are determined with phenomena such as friction, wear, lubricataion, chemical interaction with sealing fluid (corrosion), hydrodynamics and heat transfer. Therefore seal life and reliability are very much influenced by seal face material pair performance and therefore conditions in the seal must be well known. Results of testing on tribological models due to specific contact geometry and operating conditions are not satisfactory for practical comparable applications. Therefore testing on expensive real system are still required for seal material evaluation in the most cases. In the paper test rig of our own design is presented on which we simulate real operating condition of mechanical seals. The test rig is equipped with advance computer system for on-line control and monitoring of eight measured parameters which enables detail determination of conditions during seal testing and better understanding of seal performance.
Keywords: tesnila; preizkušanje; tribologija; trenje